2017
DOI: 10.1177/1362361317726245
|View full text |Cite
|
Sign up to set email alerts
|

Language profiles in young children with autism spectrum disorder: A community sample using multiple assessment instruments

Abstract: This study investigated language profiles in a community-based sample of 104 children aged 1-3 years who had been diagnosed with autism spectrum disorder using Diagnostic and Statistical Manual of Mental Disorders (5th ed.) diagnostic criteria. Language was assessed with the Mullen scales, Preschool Language Scale, fifth edition, and Vineland-II parent-report. The study aimed to determine whether the receptive-to-expressive language profile is independent from the assessment instrument used, and whether nonver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 48 publications
(124 reference statements)
1
34
1
Order By: Relevance
“…This instrument is a parent‐report standardized questionnaire that measures expressive and receptive language skills. Typically developing infants, and even infants who later exhibit language delays, typically show an early receptive advantage (i.e., total number of words comprehended minus words produced) based on the CDI; however, prior research has found that early language profiles are often atypical in HR infants (Nevill et al., ). Importantly, several studies showed that HR infants do not show such an advantage; this CDI receptive advantage metric has also been shown to be predictive of ASD outcome in HR infants, such that infants who later develop ASD have a lower receptive advantage score (Ellis Weismer, Lord, & Esler, ; Hudry et al., , ).…”
Section: Methodsmentioning
confidence: 99%
“…This instrument is a parent‐report standardized questionnaire that measures expressive and receptive language skills. Typically developing infants, and even infants who later exhibit language delays, typically show an early receptive advantage (i.e., total number of words comprehended minus words produced) based on the CDI; however, prior research has found that early language profiles are often atypical in HR infants (Nevill et al., ). Importantly, several studies showed that HR infants do not show such an advantage; this CDI receptive advantage metric has also been shown to be predictive of ASD outcome in HR infants, such that infants who later develop ASD have a lower receptive advantage score (Ellis Weismer, Lord, & Esler, ; Hudry et al., , ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have examined various potential child-based predictors of language outcomes in autistic children. Nonverbal IQ, the most frequently investigated, is a strong positive predictor of language abilities in autistic children (Anderson et al, 2007; Brignell et al, 2018; Nevill et al, 2019; Thurm et al, 2015; Weismer & Kover, 2015). For example, in a study by Weismer and Kover (2015), which employed a clinician-administered test to measure language abilities in 129 autistic children aged from 2.5 to 5.5 years, nonverbal IQ was found to be a strong predictor of language production during preschool years.…”
Section: Factors Affecting the Heterogeneity Of Expressive Language A...mentioning
confidence: 99%
“…Furthermore, considering the significant lack of social engagement in children with ASD, spontaneous communication sample may provide reliable information about functional communication (Fernandes et al, 2011). Incorporating a multi-method approach to assessment and profiling of communication in these children in a variety of context yields better representative profile (Nevill et al, 2017; Tager-Flusberg, 2000). This will also facilitate a child-centered therapeutic intervention and a better prognosis (Belkadi, 2006).…”
Section: Discussionmentioning
confidence: 99%